Synthesis of Mg15Fe materials for hydrogen storage applying ball milling procedures - Puszkiel, Julián Atilio (2010)
The effects of different synthesis procedures on the microstructure and hydrogen uptake characteristics of the Mg15Fe materials were studied. The applied processes of synthesis consisted basically on ball milling in argon atmosphere followed by a hydriding reaction. Two mill devices with distinct milling modes were employed, i.e. a low energy mill (LEM) (Magneto Uni-Ball-Mill II) and a high energy mill (HEM) (Fritsch Planetary Mill, P6). The HEM sample showed better Mg?Fe mixing degree than the sample obtained from the LEM process due to the small particles of Fe resulting from the larger amount of mechanical energy transferred to the materials by the HEM device. The better Mg?Fe contacting was responsible for the higher hydrogen capacity and faster hydrogen uptake rate of the high energy milled material. Therefore, the HEM procedure was more effective than the LEM. The hydrogen uptake properties of the HEM synthesized material were compared with other Mg-based materials obtained via inert and reactive ball milling without a subsequent activation step. This study showed that Mg15Fe mixture of powders synthesized via reactive ball milling in hydrogen (RBM?LEM) has higher hydrogen capacity (5.5 wt% H) and faster kinetics than samples with the same composition milled in argon (LEM ? 1.65 wt% H and HEM 1.87 wt% H). Nevertheless, a superior hydrogen capacity (6.5 wt% H) were obtained by adding LiBH4 to Mg15Fe via HEM in argon atmosphere.